2020
DOI: 10.1088/1755-1315/429/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Ecological status of target fishes inside and outside marine conservation area of Batbitim, Misool, Raja Ampat

Abstract: Batbitim marine conservation area (MCA) of Misool, Raja Ampat has been set as an area that is prohibited for fishing activities since 2005. The only activities allowed in that area are tourism and research activities. The difference in the management status between area inside the Batbitim MCA and outside the MCA might affect ecosystem components such as fish and coral reef in the respective area. The present study aims to investigate the ecological status of target fishes in the two areas. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In Batbitim Misool, Papua concluded that outside marine conservation areas had higher fish diversity than inside areas. The inside area had a higher coral cover which provided protection and feeding place to certain fishes, so it might be possible that there were dominant species [19]. In this research, even though there was disturbance like port activities, it does not support the dominance of one or more species.…”
Section: Abundance and Fish Communitymentioning
confidence: 69%
See 1 more Smart Citation
“…In Batbitim Misool, Papua concluded that outside marine conservation areas had higher fish diversity than inside areas. The inside area had a higher coral cover which provided protection and feeding place to certain fishes, so it might be possible that there were dominant species [19]. In this research, even though there was disturbance like port activities, it does not support the dominance of one or more species.…”
Section: Abundance and Fish Communitymentioning
confidence: 69%
“…Tropical marine fish could be differentiated into three groups: target species, indicator species, and; major species. Target species is a group of fish which are targeted by fisherman such us Acanthuridae, Haemulidae, Caesionidae, Nemipteridae, Serranidae, Scaridae, Labridae, Lethrinidae, Lutjanidae, Siganidae[19]. Indicator species are a functional group of fish that indicate coral health, like the Chaetodontidae family.…”
mentioning
confidence: 99%
“…Top-down state governance is required in order to legally recognize MPAs in many countries. However, in some instances, the pandemic has revealed the importance of devolved governance to both local communities and private enterprises: community patrollers have allowed park officials to concentrate on enforcement in distant areas, while the Misool Eco Resort in Indonesia, funded by tourism and private donors, has maintained a critical no-take zone that has seen a 250% biomass increase over the past decade [36]. With community and private sector buy-in, MPAs can be made more resilient and effective in deterring illegal and outside fishing.…”
Section: Procedural Equitymentioning
confidence: 99%
“…Studies indicated that reduced visitors improved ecosystem health in the short term, emphasizing the importance of careful spatial planning that accounts for social equity and access to protected areas [22]. Furthermore, many private foundations and trust funds were able to supply emergency funding for MPAs, but more innovative funding solutions such as conservation trust funds, "blue" bonds, and payments for ecosystem services are necessary in the future [4,36]. This will engage protected area decision makers in a complex discussion around trade-offs, that must be approached with a political and social lens, understanding who gains and who benefits from different sources of financing [39].…”
Section: Substantive Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation